Association of tibolone and dementia risk: a cohort study using Korean claims data. (3rd June 2021) - Han, Minjung; Chang, Jooyoung; Choi, Seulggie; Cho, Yoosun; Lee, Gyeongsil; Park, Sang Min
Abstract: Objective: Few studies have examined whether tibolone (TIB), a type of hormone replacement therapy widely used in Asia and Europe, affects dementia risk in postmenopausal women. Our study aims to investigate the association of TIB and dementia risk in Korean women aged 50–80 years. Methods: A population-based longitudinal study was conducted using the Korean National Health Insurance Service claims database merged with national health examination data from 2002 to 2015. Among 13, 110 participants, exposure to TIB was determined using the standardized defined daily dose (DDD) system from 2003 to 2007. Starting from 2007, participants were followed up for overall dementia, Alzheimer's disease (AD) and vascular dementia (VD) until 2015. Cox proportional hazards regression was used to determine the adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) of dementia according to TIB use. Results: TIB use was not significantly associated with the risk of total dementia (aHR = 1.040; 95% CI = 0.734–1.472; p  = .827), AD (aHR = 0.949; 95% CI = 0.652–1.381; p  = .785) and VD (aHR = 1.245; 95% CI = 0.631–2.457; p  = .528). Conclusions: Our results suggest that TIB use does not have a significant association with dementia risk. Further randomized controlled trials are necessary to elucidate the role of exogenous hormones in the development of dementia.